Harmonisasi Kearifan Lokal Nusantara dan Bali untuk Pendidikan Karakter di Sekolah Dasar: Sebuah Analisis Etno-Pedagogi - Rasna, I Wayan; Tantra, Dewa Komang; Wisudariani, Ni Made Rai (Jurnal Kajian Bali (Journal of Bali Studies); Vol 6 No 1 (2016): REFLEKSI SENI BAHASA BALI, 2016)
Abstract The present research is focused on the harmonization between Nusantara and Bali local geniuses for character education at the primary schools in Bali. The research design was purely qualitative. The informants were recruited purposively. The data were collected through in-depth interview and analyzed descriptively and coded according to text genres. Results show that the general themes and sub-themes derived from Nusantara local geniuses are well juxtaposed with the Bali geniuses. These newly derived themes and sub-themes are implemented in the curriculum at the primary schools in Bali. Character education, which include local wisdom and genius, are more reliable and valid for children in Bali. Bali’s local wisdom and genius, which adhere in the Hindu philosophy, are potentially rich for the development of character education’s themes and sub-themes. The central themes and sub-themes fleshed out from the Hindu philosophy are coherently tied into a system of meaningful moral entity. Children may learn moral characters contextually and meaningfully through the national language of Indonesia at schools. However, caution should be taken as the themes and sub-themes are critically beyondthe first and second graders’ cognitive and moral development stages.
Keywords: harmonization, nusantara and Bali local geniuses and ethnopaedagogy.